Unleashing the Power of Family Education in the Post-Covid-19 Era: Quranic and Hadith Perspective - Mukhtar Muhammad Salam; Muhammad Hasan; Samsul Bahri (SYAMIL: Journal of Islamic Education, 2023)
In the post-pandemic era, the strength of the family is crucial in facing various challenges. In this context, family education plays a vital role in shaping a strong and resilient family. With the perspective of the Quran and Hadith, family education can be optimized to produce a more robust, resilient, and positively contributing family in society. Family education can cover various aspects, including character education, religious education, and social skills, all of which can be linked to the perspective of the Quran and Hadith. Therefore, the revitalization of family education in the post-COVID-19 era is essential to create stronger and more resilient families in facing an uncertain future. The method used is a literature review and content analysis of verses from the Quran and Hadith related to family and education. The data collected were analyzed using a qualitative approach and interpreted according to the current context. The results of this study show that the Quran and Hadith provide clear and practical guidance for forming strong and resilient families in the post-COVID-19 era. The perspective of the Quran and Hadith can help families build confidence, a spirit of mutual respect, and strengthen the sense of responsibility and unity within the family. The conclusions of the findings of this study contribute that family education also help families face various challenges and complex situations in the post-COVID-19 era. Families can harness the wisdom of the Quran and Hadith to build strong foundations, foster harmonious relationships, and effectively navigate the challenges of the post-COVID-19 era. This will contribute to the development of resilient and thriving families in the broader context of society.